A comprehensive review on combustion, performance and emission aspects of higher alcohols and its additive effect on the diesel engine. (1st March 2023) - Zhang, Yanhui; Gao, Sheng; Zhang, Zhiqing; Li, Weiqing; Yuan, Tao; Tan, Dongli; Duan, Lin; Yang, Guanhua
Highlights: The development of higher alcohols of modern automobile engines is listed. The improvements of higher alcohols characteristic are discussed. Optimization applications in diesel engine are investigated. Improvement suggestions for performance enhancement of diesel engine are proposed. Abstract: The application of oxygenated alternative fuels in diesel engines is an effective way to solve the energy crisis and environmental pollution. Higher alcohols (butanol and pentanol), as oxygenated and renewable fuels, are considered as new promising alternative fuels for diesel engine due to their good physicochemical properties and excellent combustion and emission characteristics in engines. The combustion is a complex process and has a significant impact on performance and emission characteristics of compression ignition (CI) engines. There are complicated relationships among CI engine, environment and fuel physicochemical properties, which interacts with each other. Therefore, it is important to investigate the synergistic effects of alternative fuels and their additives on CI engines. In recent years, the research on the advanced alcohols and its additives had made great progress. However, few people have reviewed the synergistic effect of higher alcohols and its additives on diesel engines. Therefore, this paper takes the combustion, performance and emission aspects of higher alcohols and its additives on the diesel engine as a starting point. Firstly, the physicochemical properties and preparations of higher alcohols are described, and their advantages are highlighted. Then, the effects of higher alcohols and its additives on the combustion, performance and emission characteristics of CI engines are summarized in terms of neat fuel, dual-fuel injection and multi-fuel blends, exhaust gas recirculation (EGR), injection strategy and advanced combustion mode. Finally, some important conclusions and discussions on the future development and experimental research direction are put forward, which will be helpful for the research on the use of higher alcohol in CI engines.